The effect of pulsed electric fields pre-treatment on the volatile and phenolic profiles of Merlot grape musts at different winemaking stages and the sensory characteristics of the finished wines. (June 2021) - Arcena, Mylene Ross; Leong, Sze Ying; Then, Stephanie; Hochberg, Martin; Sack, Martin; Mueller, Georg; Sigler, Juergen; Kebede, Biniam; Silcock, Patrick; Oey, Indrawati
Abstract: This study investigated the effect of pulsed electric fields (PEF) applied at different electric field strengths (up to 41.5 kV/cm) and energy inputs (up to 49.4 kJ/kg) on the volatile and phenolic profiles of Merlot grapes at different stages of winemaking. Immediately after PEF treatment, greater amounts of anthocyanins and phenolics (e.g., catechin) were extracted while 2-hexenal (green aroma) was detected in lower concentrations in PEF-treated musts. At completion of alcoholic and malolactic fermentations, high-energy PEF treatment generally produced wines with increased anthocyanins, stilbenoids, hydroxycinnamic and hydroxybenzoic acids. A trained sensory panel assessed the sensory attributes of the finished wines using descriptive analysis. It was found that those Merlot wines vinified with PEF-treated grapes possessed higher intensities of blackcurrant flavour and odour. The intensity of spice flavour in the Merlot wines also differed significantly between the wines. Overall, PEF treatment has the capability to provide winemakers the means to tailor the extraction of phenolic compounds towards the creation of red wines with distinct sensory characteristics. Highlights: PEF intensity influenced the evolution of phenolics in Merlot during winemaking. PEF enhanced the release of phenolic compounds localised in grape seeds. Wines from PEF-treated Merlot had intense blackcurrant odour and flavour.